Towards personalized medicine for amyotrophic lateral sclerosis. (November 2021) - Cassereau, Julien; Corcia, Philippe; Reynier, Pascal
Abstract : Mohassel et al . provide unprecedented dichotomy of consequences on sphingolipid biosynthesis between pathogenic variants in the SPTLC1 gene, responsible for either amyotrophic lateral sclerosis (ALS) or hereditary sensory and autonomic neuropathy type 1 (HSAN1). Normalization of sphingolipid levels by siRNA selectively targeting the ALS mutant allele mRNA sheds light on new therapeutic approaches.